2018
DOI: 10.21475/ajcs.18.12.01.pne819
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of jambu (Acmella oleracea) using organic fertilization

Abstract: Jambu is a plant species from the northern region of Brazil, where it is widely used in food as a seasoning in typical regional dishes, and in folk medicine. The objective of this work was to evaluate the agronomic performance of jambu under organic fertilization. The experiments were conducted under field conditions for the periods January to February, 2015 (Period 1) and May to June, 2015 (Period 2), in soil classified as dystrophic yellow latosol of medium texture. The experimental design was randomized com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 10 publications
1
8
1
3
Order By: Relevance
“…In addition, it is a constituent of molecules such as chlorophyll, proteins, RNA and DNA (Taiz et al, 2017). In this sense, it can be noted that the greater availability of N had a positive effect on the growth of the aerial part of the jambu, as observed in other studies with the species (Borges et al, 2014;Souto et al, 2018;Aviz et al, 2020). It was equally detected that the application of lime associated with nitrogen fertilization obtained the maximum value of LAP from the plants, which can be explained by the increase in the levels of some essential nutrients in the soil solution (Table 2) promoted by liming, such as Ca and Mg, since these elements act in processes of protein synthesis, carbohydrates and growth regulation (Atkinson, 2014;Engels, 2012).…”
Section: Growthsupporting
confidence: 70%
“…In addition, it is a constituent of molecules such as chlorophyll, proteins, RNA and DNA (Taiz et al, 2017). In this sense, it can be noted that the greater availability of N had a positive effect on the growth of the aerial part of the jambu, as observed in other studies with the species (Borges et al, 2014;Souto et al, 2018;Aviz et al, 2020). It was equally detected that the application of lime associated with nitrogen fertilization obtained the maximum value of LAP from the plants, which can be explained by the increase in the levels of some essential nutrients in the soil solution (Table 2) promoted by liming, such as Ca and Mg, since these elements act in processes of protein synthesis, carbohydrates and growth regulation (Atkinson, 2014;Engels, 2012).…”
Section: Growthsupporting
confidence: 70%
“…These results are different from those found by Favoreto & Gilbert (2010), who observed that jambu could reach around 20 to 40 cm in height. Borges et al (2014) and Souto et al (2018) studied fertilization in the jambu crop and obtained higher plant height than that found in this study, with values of 37.36 and 35.42 cm, respectively.…”
Section: Resultscontrasting
confidence: 42%
“…Research with many cultures has been revealed that the increase on N availability in plants promote higher productivity and quality (Milhomens et al, 2015;Rós et al, 2016). Studies with jambu culture (Borges et al, 2013;Rodrigues et al, 2014;Souto et al, 2018) shown favourable response to nitrogen supplementation through soil, demonstrating high demand of N to production maintenance and quality. Although studies with jambu, linking the variation in N supply with the production of dry mass at the aerial and inflorescence part on systems more technics, as in hydroponics, which use nutritive solution instead of soil (Khan et al, 2018), are inexistent.…”
Section: Introductionmentioning
confidence: 99%